Transmission loss allocation in deregulated power system via superposition and proportional tree methods - Mustafa, Mohd Wazir; Sulaiman, Mohd Herwan (Institute of Electrical and Electronics Engineering (IEEE), 2009)
Link to publisher's homepage at http://ieeexplore.ieee.org